Implementación de un biodiogestor a partir de residuos ganaderos para uso doméstico en la hacienda La Esperanza, Calceta, Bolívar Manabí - Basurto Loor, Jhandry Manuel (2017)
The research aimed to implement a domestic tabular biodigestor of polyethylene for the production of biogas from livestock waste, in La Hacienda La Esperanza, sock, Bolivar. The method used was field quantitative as it was initially gathered information concerning the production of livestock waste, its use and benefits, then make the necessary calculations for the sizing, efficient operation and implementation of the biodigester. In the Hacienda, Gyr exists around 100 head of cattle mostly dairy and Girolando, of which 40 are pregnant with an approximate weight of 400 Kg and 60 are unmarried with 330 Kg, reaching a total of around 35800 Kg weight, which empirically generate 2864 Kg of fresh manure a day which only 716 Kg are exploitable due to grazing practices carried out on the farm. A part is used for the obtaining of Californian Vermicompost Eiseniafoetida. A quantity of 200 kg of fresh manure produces approximately 0,60 m3 of mixture per day and with a retention time of 20 days the biodigester needs a total volume of 16 m ^ 3 to obtain biogas with the necessary pressure for their respective use; biogas production started after 24 days established, it is estimated that it was generated around was 7,60 m3 de biogas a day, in such a way that it was used on a stove for cooking.